2013
DOI: 10.1155/2013/659254
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Low Concentrations of Decitabine and SAHA Causes Cell Death in Leukemic Cell Lines but Not in Normal Peripheral Blood Lymphocytes

Abstract: Epigenetic therapy reverting aberrant acetylation or methylation offers the possibility to target preferentially tumor cells and to preserve normal cells. Combination epigenetic therapy may further improve the effect of individual drugs. We investigated combined action of demethylating agent decitabine and histone deacetylase inhibitor SAHA (Vorinostat) on different leukemic cell lines in comparison with peripheral blood lymphocytes. Large decrease of viability, as well as huge p21WAF1 induction, reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…This result explains, at least in part, the greater degree of apoptosis induction in the U937 cell line by the epigenetic combination therapy that is stimulating both the intrinsic and the extrinsic apoptotic pathways. In accordance with our results, a previous study showed that the treatment of AML cell lines, CML-T1 and HL-60, with a combination of SAHA and DAC upregulated the cleavage of procaspase 3 and 7 and induced the p53-dependent apoptotic way of cell death in CML-T1 [46].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result explains, at least in part, the greater degree of apoptosis induction in the U937 cell line by the epigenetic combination therapy that is stimulating both the intrinsic and the extrinsic apoptotic pathways. In accordance with our results, a previous study showed that the treatment of AML cell lines, CML-T1 and HL-60, with a combination of SAHA and DAC upregulated the cleavage of procaspase 3 and 7 and induced the p53-dependent apoptotic way of cell death in CML-T1 [46].…”
Section: Discussionsupporting
confidence: 93%
“…We observed a significant time-and dose-dependent inhibition of cell growth using either epigenetic modulator. Previous reports have documented that inhibitors of HDACs and DNMTs have selective, anti-proliferative effects on multiple cancer cell lines, including AML cell lines, while maintaining normal viability and proliferation of normal blood cells [25,45,46]. The HDAC inhibitors-valproic acid, trichostatin A, and sodium butyrate-inhibited leukemic cell proliferation in a dose-dependent manner [45].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of proapototic BAX protein only moderately increased in response to DAC + SAHA + ATRA treatment of HL-60 cells, but its mitochondrial localization in apoptotic cells indicating mitochondrial apoptotic pathway was found like it was documented in DAC + SAHA treated cells [5]. Negative correlation between survivin and BAX expression was detected in DAC + SAHA + ATRA-treated cells by flow-cytometry confirming again the relationship between loss of survivin expression and apoptosis (Figure 5).…”
Section: Discussionsupporting
confidence: 61%
“…Current cancer therapy should satisfy requirements for targeted elimination of cancer cells simultaneously with life-compatible adverse effects [ 10 ]. One of the main tenets of cancer therapeutics is that combinations of anticancer agents with different targets or different mechanisms of action and varied normal tissue toxicities will produce better therapeutic outcomes [ 11 ] by decreasing single drugs doses and minimizing or slowing drug resistance development.…”
Section: Introductionmentioning
confidence: 99%